Impact of the Hydroxyapatite Concentration on the Mechanical properties and accelerated degradation of PCL-based Scaffolds in the Bone Tissues Engineering . - Mishbak, Hussein (University of Thi-Qar Journal, 2026)
Polycaprolactone (PCL) has become one of the most prominent biomaterials for bone tissue engineering scaffolds due to its biocompatibility, FDA approval and durability of mechanical properties. However, pure PCL scaffolds have some inherent limitations such as high hydrophobicity and inadequate bioactivity. This study overcomes these limitations by incorporating hydroxyapatite (HA) nanoparticles in PCL based composite scaffolds at different concentrations (10% and 20% w/w). PCL/HA composite scaffolds and pure PCL controls were produced by the solvent casting and salt leaching method and fully characterized. The addition of HA improved both tensile and compressive mechanical properties of the composites in a concentration dependent manner. PCL/HA (20% w/w) scaffolds showed tensile strength of 16.5 MPa and compressive strength of 18.4 MPa which were 52.8% and 60.0% respectively higher than pure PCL. All scaffolds had well-interconnected porous architectures that are suitable for the infiltration of cells and the transport of nutrients. Accelerated degradation studies with 5.0 M NaOH solution showed that the effect of HA incorporation significantly accelerated degradation of the scaffold in a concentration-dependent manner with PCL/HA (20% w/w) showing 25% mass loss over five days compared to less than 4% for pure PCL. This accelerated degradation is attributed to the hydrophilic nature of HA particles to act as absorbances and to infiltrate the corrosive medium into the scaffold substance coupled with increased internal surface area due to HA-induced micropores on strut walls. These findings indicate that PCL/HA composite scaffolds provide an acceptable compromise between improved mechanical properties and tunable degradation behavior, and could be good candidates for load-bearing bone tissue engineering applications in which mechanical support and controlled tissue integration are important.